Kontribusi Pendidikan Islam Modern di Indonesia: Studi Kasus Pesantren Riyadlul Ulum Wadda’wah, Condong, Tasikmalaya - Dewi Aprilia Ningrum; Rifa Tsamrotus Sa’adah (JURNAL INDO-ISLAMIKA, 2020)
This study discusses Riyadlul Ulum Wadda’wah Condong Islamic boarding school’s best practice in learning foreign languages and adopting modern values in its education management system. The experience of this Islamic Boarding School which is known also as Pondok Pesantren Condong, Tasikmalaya, is considered important to be shared to others due to its new policy which blended three existing education systems in the country in spite of the fact that many scholars have overlooked it. The boarding school retained the curriculum of traditional pesantren, adopts the modern Islamic boarding school system of Darussalam Gontor, and applies also general education systems for junior and senior high school system. Using a descriptive-analytic method, this study examines how Condong Islamic Boarding School carried out its modernization program both in learning foreign languages (Arabic and English language) and in coverging three models of education -curriculum of traditional pesantren, Darussalam Gontor’s modern, and general education system for its education program and governance. In so doing, the main data of the study were collected from observation and experience of the writers while i was a student of this pesantren for six years 2007-2012. The study finds that Condong Islamic Boarding School  has successfully transformed its boarding school from passive traditional Islamic boarding school to progressive and modern one. It also finds that  the application of new learning foreign languages and of modern values in Condong Islamic boarding school affects significantly to the progress and transformation of students to  achieve their and the school’s expected outcomes.